Decoding the Magic Formula: Navigating the Complex World of Stock Trading - Wicaksono, Soetam Rizky; Setiawan, Rudy (Universitas Muhammadiyah Ponorogo, 2024)
Stock trading is complicated and risky. Investors' conditions, aspirations, and viewpoints shape their journeys. This article examines stock trading and investing, focusing on Joel Greenblatt's